Pertanggungjawaban Perusahaan Kelapa Sawit Atas Kerusakan Jalan Kabupaten Perspektif Maslahah Mursalah - Sari, Emilia; Adly, Muhammad Amar (Universitas Muhammadiyah Ponorogo, 2025)
PT Perkebunan Nusantara (PTPN) IV Tinjowan is a palm oil company that has the responsibility to improve the welfare of the community around the plantation in various aspects. Research at PT Perkebunan Nusantara (PTPN) IV Tinjowan focuses on priorities for the community around the palm oil plantation, because this company is engaged in the economy. However, there are obstacles in the implementation of some of the company's programs, especially in the infrastructure sector. The method used in this study was a direct field survey and structured interviews with village officials. The field survey was conducted to see the condition of road damage (traffic), while structured interviews were conducted with local village officials, namely parties in the community who are considered to have knowledge and know in detail about the programs that have not been running. The results of the study showed that the PTPN IV Tinjowan program had not been implemented properly in the field of road infrastructure (traffic). There were several programs that had not been evenly distributed throughout the community, so further socialization was needed.